2014
DOI: 10.1016/j.joi.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

On the citation lifecycle of papers with delayed recognition

Abstract: Delayed recognition is a concept applied to articles that receive very few to no citations for a certain period of time following publication, before becoming actively cited. To determine whether such a time spent in relative obscurity had an effect on subsequent citation patterns, we selected articles that received no citations before the passage of ten full years since publication, investigated the subsequent yearly citations received over a period of 37 years and compared them with the citations received by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Stent [ 5 ] discusses ‘prematurity’ in scientific discovery. Recent studies focus on the probability of becoming highly cited in later years [ 6 ]; the occurrence of delayed recognition [ 7 ]; SBs in psychology [ 8 ] and in physics (‘revived classics’ [ 9 ]; an example of awaked application-oriented work [ 10 ]); the probability of SBs [ 11 ]; a typology of behavioral patterns in citation histories of SBs [ 12 , 13 ]; extreme historical cases [ 14 ]; the reasons for awakening [ 15 ]; SBs with a short leaping immediately after publication [ 16 , 17 ]; different types of SBs in a specific journal [ 18 ]; SBs and ‘durability’ of scientific publications in general and its effects on research performance assessments by citation analysis [ 19 21 ]; SBs in the work of Nobel Prize winners and the dependence of the awake intensity on the citation distribution within the sleeping period [ 22 ]; the identification of the ‘princes’ [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stent [ 5 ] discusses ‘prematurity’ in scientific discovery. Recent studies focus on the probability of becoming highly cited in later years [ 6 ]; the occurrence of delayed recognition [ 7 ]; SBs in psychology [ 8 ] and in physics (‘revived classics’ [ 9 ]; an example of awaked application-oriented work [ 10 ]); the probability of SBs [ 11 ]; a typology of behavioral patterns in citation histories of SBs [ 12 , 13 ]; extreme historical cases [ 14 ]; the reasons for awakening [ 15 ]; SBs with a short leaping immediately after publication [ 16 , 17 ]; different types of SBs in a specific journal [ 18 ]; SBs and ‘durability’ of scientific publications in general and its effects on research performance assessments by citation analysis [ 19 21 ]; SBs in the work of Nobel Prize winners and the dependence of the awake intensity on the citation distribution within the sleeping period [ 22 ]; the identification of the ‘princes’ [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rarity and thus likely idiosyncrasy of “hibernators” is, however, such that to gather a statistically interesting sample size for a proper study, a very large population is required, as are solid selection criteria (Lachance & Larivière, ). This remark holds even more for a combination with another rare phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Lachance and Larivière () studied so‐called sleepers, a group of papers that received their first citation(s) 10 full years or more since their publication. This group includes hibernators, but also other less‐cited articles.…”
Section: Two Special Types Of Articlesmentioning
confidence: 99%
“…Li et al (2014) addressed the citation age distribution during the sleeping period, which they called "heartbeat spectrum", of sleeping papers and revealed that papers with "late heartbeats" have much higher awakening probability (more likely to become sleeping beauties) than those with "early heartbeats." Lachance and Larivière (2014) extracted "sleepers" from papers published during 1963-1975 as papers which received no citation for ten years or more since publication but obtain some citations hence, and compared citation pattern of the sleepers (about 5% of the all papers) with that of the non-sleeper papers of the same period (control group). Although the citation age distribution of sleepers after awakening showed a gradual decline in general similar to the control group, but the highly-cited sleepers (i.e., sleeping beauties) showed no decline but even increase, differing from patterns of the control group.…”
Section: Classification Of Papers By Their Citation Durability and Inmentioning
confidence: 99%